OBSERVATIONS ON THE IMMUNOLOGICAL RELATION OF POLIOMYELITIS TO LOUPING ILL - Schwentker, F. F. (The Rockefeller University Press, 1933)
The results of the work presented in the present paper show that louping ill and poliomyelitis immunologically are not closely related. Although relatively few experiments were performed, the data obtained were sufficiently decisive for our purposes. Certainly nothing was found to indicate that one might be able to immunize human beings against poliomyelitis by the use of louping ill virus. In addition to the negative findings, a certain amount of useful information was also secured, namely, (1) monkeys can be solidly immunized against louping ill by intraperitoneal injections of virus and partially protected by intramuscular administrations of the active agent, (2) during the process of immunization no signs of involvement of the central nervous system are manifested, and (3) sera from monkeys immunized in the manner described contain antibodies capable of neutralizing the virus.